Acute gastrointestinal bleeding caused by Jejunojejunal intussusception in an adult: a case report and literature review - Ebrahimian, Manoochehr; Kialashaki, Mehrnoosh (Student Research in Translational Medicine, 2020)
Intussusception in adults is an uncommon entity with various clinical manifestations and complications such as acute gastrointestinal bleeding. We reported a 30-year-old man who referred to our hospital with loss of consciousness and developed two separate courses of acute gastrointestinal bleeding after admission. During second surgery, we came across a jejunojejunal intussusception as the main cause of gastrointestinal bleeding. Hereby, we reviewed and analyzed our experience in the management of this disease and also compared our findings with respective literature and other studies.